Hubungan Perubahan Berat Badan, Hipertensi dan Ketidakteraturan Siklus Haid dengan Lamanya Penggunaan Kontrasepsi Suntik 3 Bulan - Laily Selviana; Murdiningsih Murdiningsih; Rizki Amalia (Universitas Batanghari Jambi, 2022)
Acording to the World Health Organization, hormonal contraception as a means of contraception isincreasing sharply. The most use of hormonal contraception isinjectable contraceptives, whichis 38.3% and pills as much as 27.7% and implants as much as 23.6%. body weight, hypertension and menstrual cycle irregularities with the duration of the use of contraceptive injections for 3 months at the UPTD of Daya Utama Health Center, Banyuasin Regency in 2021. This type of research used an analytic survey method using a crosss ectional design. The population in this study were mothers who used 3- month injectable contraception, totaling 81 respondents and taken using proportional random sampling technique. Data were analyzed by chi-square statistical test. The results showed that there was asignificant relationship between changes in weight, hypertension and menstrual cycle irregularities. The conclusion in this study was that there was a relationship between changes in body weight, hypertension and menstrual cycle irregularities with the duration of the use of injectable contraception for 3 months in Banyuasin districtin 2021.